Halotolerant Rhizobacteria Isolated from Salinity-Impacted Marginal Soils: Characterization and Potential for Plant Growth Promotion - Syarafina Ratna Putri; Laurentius Hartanto Nugroho; Sukirno Sukirno; Endah Retnaningrum (Universitas Sebelas Maret, 2025)
Soil salinity is a significant constraint on crop productivity, particularly in marginal lands, and sustainable biological approaches are needed to mitigate its impact. Plant growth-promoting rhizobacteria (PGPR) with halotolerance represent promising candidates for enhancing plant resilience under saline stress. This study aimed to isolate halotolerant PGPR from saline-impacted soils in Pekalongan, Indonesia, and evaluate their potential to improve plant growth under salinity stress. Five bacterial isolates (WN-01 to WN-05) were successfully obtained. The isolates displayed multiple PGPR traits, including nitrogen fixation, phosphate solubilization, indole-3-acetic acid (IAA) synthesis, siderophore release, cellulase activity, 1-aminocyclopropane-1-carboxylate (ACC) deaminase activity, exopolysaccharide production, and tolerance to salinity up to 9% NaCl. Molecular identification confirmed the isolates as Bacillus subtilis (WN-01), Priestia megaterium (WN-02), Pseudomonas segetis (WN-03), Bacillus pumilus (WN-04), and Bacillus cereus (WN-05). Compatibility analysis indicated their potential to be formulated as a consortium bioinoculant. In vivo pot experiments using sweet maize (Zea mays saccharata var. Bonanza F1) under saline conditions (4 dS m-1) showed that consortium application, especially at 10⁸ CFU ml-1, significantly enhanced plant height, leaf surface area, and chlorophyll content. Moreover, the total microbial population in soil increased proportionally with inoculum density, with the highest values recorded in the 10⁸ CFU ml-1 treatment. These findings demonstrate that local halotolerant PGPR have strong potential as bioinoculants to support crop growth and soil health in saline-impacted marginal lands.